110k views
0 votes
Help---------------​

Help---------------​-example-1

1 Answer

4 votes

Answer:

C. (f - g)(x) = 3ˣ - 2x + 14

General Formulas and Concepts:

Pre-Algebra

  • Distributive Property

Algebra I

  • Function Notation
  • Combining Like Terms

Explanation:

Step 1: Define

f(x) = 3ˣ + 10

g(x) = 2x - 4

(f - g)(x) is f(x) - g(x)

Step 2: Find (f - g)(x)

  1. Substitute: (f - g)(x) = 3ˣ + 10 - (2x - 4)
  2. Distribute -1: (f - g)(x) = 3ˣ + 10 - 2x + 4
  3. Combine like terms: (f - g)(x) = 3ˣ - 2x + 14
User Pooshonk
by
5.0k points